Między polityką a estetyką — o recepcji i przekładzie Przedstawienia „Hamleta” we wsi Głucha Dolna Ivo Brešana - Małczak, Leszek (Przekłady Literatur Słowiańskich, 2012)
Between politics and aesthetic — about the reception and translation of Brešan’s Predstava “Hamleta” u selu Mrduša Donja Predstava “Hamleta” u selu Mrduša Donja is the most popular Croatian and former Yugoslav drama and play in Poland. The Polish translation of Predstva… was published in the magazine Dialog (nr. 1/1975) and then in 1988 in the book Antologia współczesnego dramatu jugosłowiańskiego. The first play was realised in Zielona Góra in 1975, the last one in Krakow in 2009. In total, Brešan’s text was played in 16 Polish theatres. The subject of the analisys is the reception and translation which oscillates between two opposite poles: universal interpetation which emphasises human, timeless meaning of the drama and political interpretation which emphasises political and social context presented in the drama. Key words: Ivo Brešan, Predstava “Hamleta” u selu Mrduša Donja, reception, translation, politics, aesthetic.